Dengue fever in Saudi Arabia: A review of environmental and population factors impacting emergence and spread. Issue 30 (July 2019) - Altassan, Kholood K.; Morin, Cory; Shocket, Marta S.; Ebi, Kris; Hess, Jeremy
Abstract: Dengue fever (DF) is the most important mosquito-transmitted viral disease causing a large economic and disease burden in many parts of the world. Most DF research focuses on Latin America and Asia, where burdens are highest. There is a critical need for studies in other regions where DF is an important public health problem but less well-characterized and can differ, such as the Middle East. The first documented case of DF in Saudi Arabia occurred in 1993. After a decade of sporadic outbreaks, the disease was declared endemic in 2004 and this designation persists. Climate, sociodemographic factors, and increasing urbanization impact the spread of DF in Saudi Arabia, as in other areas. However, DF transmission in Saudi Arabia is also affected by several unique factors, including large numbers of migrant workers and religious pilgrims from other dengue endemic areas across the Middle East, North Africa, and Asia. Important knowledge gaps relate to the role of climatic factors as drivers of DF in Saudi Arabia and the role of foreign workers and pilgrims in the original and continuous importation of dengue virus. Filling these gaps would improve health system preparedness.